6y-4-3y+1=12

Simple and best practice solution for 6y-4-3y+1=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-4-3y+1=12 equation:


Simplifying
6y + -4 + -3y + 1 = 12

Reorder the terms:
-4 + 1 + 6y + -3y = 12

Combine like terms: -4 + 1 = -3
-3 + 6y + -3y = 12

Combine like terms: 6y + -3y = 3y
-3 + 3y = 12

Solving
-3 + 3y = 12

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 3y = 12 + 3

Combine like terms: -3 + 3 = 0
0 + 3y = 12 + 3
3y = 12 + 3

Combine like terms: 12 + 3 = 15
3y = 15

Divide each side by '3'.
y = 5

Simplifying
y = 5

 

You can always share this solution

See similar equations:

| 6x^2-2x-28=0 | | 4x-2x=56 | | -x^2+28x+29=0 | | 4x-8(-2)=16 | | 7x+9=2x-6 | | 5x-3=x+1 | | 6x-3=3x+6 | | 7x^2-19x-6=0 | | 3(x+1)=x-5 | | (x+3)(4x-5)=0 | | .33(24p-66)=3p+43 | | 19-(-8)-(-14)= | | 0=.5x-1 | | X+x+12=64 | | 5x-5*-10=25 | | 5x-5*0=25 | | 5*0-5y=25 | | x^3-7x^2+36=0 | | 5=11 | | 2x+5=68 | | 15+49(m-2)=21 | | n+3.9=10.2 | | s-8=11 | | 3(x+6)+4(2x-5)=0 | | 0.125(w-7)=5 | | 2x+8=4x | | 2(3-4y)=-10 | | 0.333333333(m+6)=4 | | 20-5=1x+21 | | 48=2a+4a | | 0.25(d-5)=1 | | 15y=2(7y-4) | | -a+9=25 | | 15=-z+8 | | -1=-n-3 | | -9=-a+16 | | 4=3x-14 | | -y-52=33 | | -p-24=-8 | | 4(x+8)=24-8x | | 6x+1-5x=7.2 | | 2x^4+x^2=4 | | x+x(0.15)=40 | | 2x^4+x^2=2 | | 2x^4+x^2=0 | | 2x^4+x^2=32 | | x^4+x^3+x^2+x=0 | | 3b+7=16 | | 5x+(8x+x)=10 | | 2(3p+2)=22 | | 49x^2-33=56x | | 4n=2n+17 | | x^4-11x^2+28=0 | | X^2-x=20 | | x^4+11x+30=0 | | 6x-1=15x-64 | | 4x+16=14x-64 | | (4x+5)(4x-5)=0 | | y+6x=0 | | 3x+9-6(6+8)=7(7+3) | | y=6x+1 | | 3X-27=21 | | x^2+13x=0 | | -y^2-13y=0 | | -y^2-13=0 |

Equations solver categories